Relational capital and strategic orientations as antecedents of innovation: Evidence from Mexican SMEs - Edgar R. Ramírez-Solis; Joan Llonch-Andreu; Alberto D. Malpica-Romero (Journal of Innovation and Entrepreneurship, 2022)
Questions "Where does innovation initiate in a company?" and "How can a small and medium-sized enterprise (SME) leverage its different resources to enhance its innovation capabilities to outperform its competitors?" remain unanswered to date. Accordingly, this study examined the relationship between the firm's relational capital and fundamental strategic orientations that a firm can adopt and how these different orientations affect innovation and organizational performance. The target sample included 360 Mexican SMEs who completed a pen-and-pencil questionnaire conducted at the four main cities of this country. Structural equation modeling was performed, and results revealed a strong positive effect of relational capital over all four strategic orientations considered in this study. However, mixed findings of strategic orientations and innovation were obtained. Although market and entrepreneurial orientation positively influenced innovation, a negative relationship was found between learning orientation and innovation and a nonsignificant relationship between technology orientation and innovation. As expected, innovation positively influenced the performance of SMEs. This study offers essential academic contributions and interesting managerial insights to improve performance using relational capital through innovation and strategic orientations. Therefore, we propose relational capital as an underexploited resource and a source of innovation for SMEs.
Keywords: 650; Innovation; Mexico; Relational capital; SMEs; Strategic orientations